A Gendered Analysis of ‘Time Poverty’ – The Importance of Infrastructure. - Lawson, D (GPRG, 2007)
This paper uses a combination of nationally representative individual level time use data combined with household and community data to further our understanding of time use, and how infrastructure impacts on gender disaggregated time poverty. With a common, and growing, perception in the empirical literature being that Sub Saharan African females are typically disadvantaged in market based activities because of the large time burden of having to undertake both formal work and domestic duties, it is important to understand some of these key processes and issues that underpin, and link with, poverty reduction. Using nationally representative from Lesotho we are able to provide unique insights into gender related, formal and informal, work allocations and specifically obtain insights regarding the main determinants of those who are 'time poor' and how key infrastructural elements impact on this.